CORRELATION BETWEEN SOIL NUTRIENTS AND SOIL-BORNE MYCOFLORA IN WHEAT-RICE CROPPING SYSTEM OF PUNJAB, PAKISTAN - A. Kanwal; A. Javaid; R. Mahmood; N. Akhtar (Journal of Animal and Plant Sciences, 2017)
Soil samples were collected from 12 wheat fields with wheat-rice cropping history, from Lahore, Sheikhupura and Sialkot districts. Electrical conductivity (EC), pH, organic matter, nitrogen (N), phosphorus (P) and potassium (K) of soil samples ranged from 533–2360 µS cm-1, 6.9–9.0, 0.69–2.02%, 0.03–0.10%, 4–225 ppm and 100–650 ppm, respectively. Eighteen fungal species belonging to Aspergilus, Alternaria, Cladosporium, Drechslera, Emericella, Fusarium, Mortierella, Mucor and Penicillium genera were isolated from soil samples. There was a significant variation in number of colonies of total, saprophytic and pathogenic fungi among the soil samples. Total number of fungal colonies, and number of colonies of saprophytic and pathogenic fungi ranged from 414–1872 g-1, 412–1728 g-1 and 36–234 g-1 of soil, respectively, in different soil samples. Total number of fungal colonies and number of colonies of saprophytic fungi were significantly and negatively correlated with organic matter and N, and significantly and positively correlated with EC and K, respectively. Correlation between number of colonies of pathogenic fungi and different soil characteristics was insignificant. This study concludes that saprophytic fungi are adversely affected by organic matter and N, and are stimulated by K in rice wheat cropping system in fertile lands of central Punjab.
Keywords: Correlation; soil-borne mycoflora; soil nutrients; wheat-rice cropping